Basabali Wiki, Penggunaan Website Kamus Digital Sebagai Langkah untuk Melestarikan Bahasa Bali - Ardyaningtyas, Riri (JOEAI (Journal of Education and Instruction), 2023)
This study aims to discuss the use of the website by the BASAbali Wiki community to preserve Balinese language, script and cultural literature. This research uses a case study approach by analyzing digital dictionaries and supporting features provided by the BASAbali Wiki website, and in-depth interviews with one of the BASAbali Wiki community administrators. The results of the study show that the BASAbali Wiki community is able to utilize information technology through the process of digitizing dictionaries and libraries through the website by involving practitioners and community leaders who are experts in their fields. The public can also actively participate in website development by adding data or editing data that is already available. With the presence of a digital Balinese dictionary and other supporting features on the BASAbali Wiki website, it is hoped that it can increase the frequency of use of the Balinese language by Balinese people, as well as introduce Balinese language and culture on a massive and more in-depth basis to the general public. From the results of the study it can be concluded that the BASAbali Wiki organization actively participates in efforts to preserve Balinese language, script, culture and literature by utilizing digital technology Keywords: BASAbali WIKI, Balinese Language, Digitalization, Website